‘Something in the way she moves’: The functional significance of flexibility in the multiple roles of protein disulfide isomerase (PDI) - Freedman, Robert B. (Biochim Biophys Acta, 2017)
Protein disulfide isomerase (PDI) has diverse functions in the endoplasmic reticulum as catalyst of redox transfer, disulfide isomerization and oxidative protein folding, as molecular chaperone and in multi-subunit complexes. It interacts with an extraordinarily wide range of substrate and partner proteins, but there is only limited structural information on these interactions. Extensive evidence on the flexibility of PDI in solution is not matched by any detailed picture of the scope of its motion. A new rapid method for simulating the motion of large proteins provides detailed molecular trajectories for PDI demonstrating extensive changes in the relative orientation of its four domains, great variation in the distances between key sites and internal motion within the core ligand-binding domain. The review shows that these simulations are consistent with experimental evidence and provide insight into the functional capabilities conferred by the extensive flexible motion of PDI.